Strategi Promosi Tari Tortor sebagai Daya Tarik Wisata Budaya Berkelanjutan (Studi Kasus di Provinsi DKI Jakarta) - Veronica, Veronica (Jurnal Ilmiah Global Education, 2024)
The Tortor Dance Performance has a cultural tourism attraction, and its role in increasing tourism is no less important when compared to other cultural attractions belonging to the Batak Tribe. This research is interesting because it was conducted in DKI Jakarta, as it is known that Jakarta is the national capital as a representation of a mini-Indonesia. Jakarta no longer only belongs to the Betawi tribe, but also to immigrant tribes who have lived in Jakarta for a long time, including the Batak tribe. The analytical method used is SWOT using a qualitative approach through data collection techniques through interviews. The results of this study stated that the potential for the Cultural Arts of the Tortor Dance in DKI Jakarta obtained positive results, meaning that the Tortor Dance has good potential, even though this dance originates from North Sumatra Province, the community still has high interest in this traditional dance. The role of stakeholders in DKI Jakarta towards the Tortor Dance Cultural Arts is considered very good, but there has not been a significant role in supporting the preservation of the Tortor Dance Cultural Arts in Jakarta. The strategy for promoting the Tortor Dance Cultural Arts in DKI Jakarta by using information technology is considered the most appropriate form to reach all levels of society. In an effort to increase the interest of the younger generation in terms of publication and information, stakeholders disseminate information about the Tortor Dance Cultural Arts through websites and social media such as Instagram, Twitter, TikTok, YouTube, and linked in.